Molecular Dynamics Simulation Studies on the Stability and Dissociation of Clathrate Hydrates of Single and Double Greenhouse Gases - Sinehbaghizadeh, Saeid; Saptoro, Agus; Amjad-Iranagh, S.; Tze Tiong, Angnes Ngieng; Mohammadi, A.H. (AMER CHEMICAL SOC, 2022)
Comprehending and controlling the stability and dissociation of greenhouse gases hydrates are critical for a variety of hydrate-based industrial applications, such as greenhouse gas separation, sequestration, or utilization. Although the promotion effects of greenhouse F-gases (F-promoters) and new cyclic promoters on CO2hydrates have been acknowledged, the involved molecular mechanisms are poorly understood. This work was therefore conducted to investigate the intermolecular mechanisms of the properties of CO2and NF3hydrates using molecular dynamics (MD) simulation to better understand their stability and dissociation and the effects of thermodynamic conditions as well as cage occupancy. In addition, the stability of CO2/CO2+ CH4hydrates in the presence of seven thermodynamic hydrate promoters (THPs) from different molecular groups or substituents was evaluated. Results reveal that after the breakup of the hydrate, the propensity of NF3to form nanobubbles is more than that of CO2molecules. The relative concentration distribution of partially occupied hydrates was also found to be greater than that of completely filled by guest gases. MD simulation results of CO2double and mixed hydrates also show that the type of large molecular guests in the large cages plays a major role in the stabilization of the clathrate hydrate network. The structural properties, however, indicate that the resistance against being dissociated for CO2+ promoter can be somewhat increased when half of the CO2molecules in small cages is replaced by CH4. In addition, the existence of neopentyl alcohol in large cavities was found to facilitate the process of hydrate dissociation by making new hydrogen bonds between hydroxyl groups and water molecules. Among studied systems with THPs, cyclopentane, and cyclohexane in comparison with F-promoters seem to be more susceptible to maintaining the stability of CO2clathrate hydrate.